Executive Committee Minutes 2011-03-17 - Academic Senate:::::::::
Agenda approved. Minutes delayed. Chair Report. Chair-Elect Report. Consultation re: naming opportunity at GMC. President Report. FSAC response to new job description of Associate Vice President of Academic Affairs. Academic Calendar Change Feedback from Standing Committees. Counseling and Psychological Services fee. CFA Report. Latin American Studies minor reorganization approved as information item. FASC Endorsement Language for FSSP Report. Senate agenda approved.